The Relationship Between Environmental Sanitation And Inpatient Satisfaction at North Buton District General Hospital - Febryani Alimuddin Lauku; Ramadhan Tosepu; Jafriati (Miracle Journal of Public Health, 2026)
Patient satisfaction is affected by the hospital environment, facilities, and the healthcare services offered. Properly addressing hospital environmental conditions, also known as environmental sanitation, is essential to providing a clean and comfortable environment that prevents cross-infection and contamination. Common environmental sanitation problems at RSUD Buton Utara (Buton Utara Regional General Hospital) include water and sanitation, pest and vector control, building and facility sanitation, and environmental cleanliness. This study aims to determine the association between inpatient satisfaction and hospital environmental sanitation at RSUD Buton Utara. A cross-sectional research design and quantitative methodology were employed. The sample included 118 patients, and the population consisted of 167 patients. Patient satisfaction was the dependent variable. The independent factors were water and air quality, food quality, sanitation of buildings and facilities, waste safety, and the presence of pests and vectors. There was an association between inpatient satisfaction and water and sanitation (p = 0.016), air and sanitation (p = 0.004), building and facility conditions (p = 0.000), waste safety (p = 0.009), and the presence of pests and vectors (p = 0.000). However, there was no association between patient satisfaction and food sanitation (p = 1.000). RSUD Buton Utara needs to provide, maintain, and enhance facilities that can improve hospital environmental sanitation.